Factors associated with contraception use among reproductive age women in Rwanda: An analysis of demographic and health survey data 2019–2020 - Delphine Cyuzuzo; Valens Munyembaraga; Aimable Gasana; Wen-Chun Liao (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Contraception is essential for preventing unintended pregnancies, averting about 230 million births and saving over 272,000 mothers’ lives globally each year. Although 40% of pregnancies worldwide are unintended, contraceptive use in Africa remains low, increasing only from 23.9% in 2012 to 28.5% in 2017. In contrast, Rwanda has seen a major rise in contraceptive uptake, from 17% in 2005 to 64% in 2020. This retrospective study examined factors influencing contraceptive use among Rwandan women of reproductive age using data from the 2019–2020 Demographic and Health Survey. Most participants were 35–39 years old, lived in rural areas, had primary education, were married, and had 4–6 children. Multivariate analysis showed that age, marital status, number of children ever born, education, religion, and wealth index were significantly associated with modern and current contraceptive use (p < .001), while residence showed no association. These findings underscore the importance of sociodemographic factors for strengthening family planning policies in Rwanda.